Comprehensive Review of the Latest Investigations of the Health-Enhancing Effects of Selected Properties of Arthrospira and Spirulina Microalgae on Skin - Mirosława Chwil; Rok Mihelič; Renata Matraszek-Gawron; Paulina Terlecka; Michał M. Skoczylas; Karol Terlecki (MDPI AG, 2024)
Arthospira platensis and Spirulina platensis microalgae are a rich source of pro-health metabolites (% d.m.): proteins (50.0-71.3/46.0-63.0), carbohydrates (16.0-20.0/12.0-17.0), fats (0.9-14.2/6.4-14.3), polyphenolic compounds and phenols (7.3-33.2/7.8-44.5 and 4.2/0.3 mg GAE/g), and flavonoids (1.9/0.2 QUE/g) used in pharmaceutical and cosmetic formulations. This review summarises the research on the chemical profile, therapeutic effects in dermatological problems, application of Arthrospira and Spirulina microalgae, and contraindications to their use. The pro-health properties of these microalgae were analysed based on the relevant literature from 2019 to 2024. The antiviral mechanism of microalgal activity involves the inhibition of viral replication and enhancement of immunity. The anti-acne activity is attributed to alkaloids, alkanes, phenols, alkenes, phycocyanins, phthalates, tannins, carboxylic and phthalic acids, saponins, and steroids. The antibacterial activity generally depends on the components and structure of the bacterial cell wall. Their healing effect results from the inhibition of inflammatory and apoptotic processes, reduction of pro-inflammatory cytokines, stimulation of angiogenesis, and proliferation of fibroblasts and keratinocytes. The photoprotective action is regulated by amino acids, phlorotannins, carotenoids, mycosporins, and polyphenols inhibiting the production of tyrosinase, pro-inflammatory cytokines, and free oxygen radicals in fibroblasts and the stimulation of collagen production. Microalgae are promising molecular ingredients in innovative formulations of parapharmaceuticals and cosmetics used in the prophylaxis and therapy of dermatological problems. This review shows the application of spirulina-based commercial skin-care products as well as the safety and contraindications of spirulina use. Furthermore, the main directions for future studies of the pro-health suitability of microalgae exerting multidirectional effects on human skin are presented.